The Potential of Snake Fruit Peel Extract As A Supplement to Metformin For Antidiabetic Therapy and For Preventing Cell Apoptosis: A Systematic Review - Anditri Weningtyas (Universitas Pahlawan Tuanku Tambusai, 2026)
The white race, especially the adult population, has a prevalence of type 2 diabetes ranging from 3% to 6%. The diabetes frequency in Singapore has greatly escalated in the past ten years. Despite being called a tropical country, Indonesia is the world's second-largest contributor to biodiversity (following Brazil). Approximately 2,500 species of plants are classified as herbs in Indonesia, which has about 30,000 species. An example of these herbs is snake fruit that gives numerous pharmacological effects, such as immunostimulator, antioxidant, antidiabetic, and it improves lipid profile. A lot of types of snake fruit can be found in Indonesia, and their various content are likely to appear due to the different types of snake fruit's physical conditions, as indicated in the previous research. Phenolic compounds and flavonoid groups can inhibit the α-glucosidase enzymes due to being capable of neutralize free radicals, and eventually, pancreatic beta cell apoptosis can be prevented. Methods use Systematic Review by conducting literature searches using PubMed and Ebsco. The literature discusses snake fruit, antidiabetic and cell apoptosis. There are six studies, concluding that snake fruit can be antidiabetic and it prevents cell apoptosis. Snake fruit can be an antidiabetic alternative in the treatment of diabetes, particularly in preventing cell apoptosis.